Molecular identification of pathogenic bacteria causing foodborne disease in Caulerpa racemosa - Kartika, Aprilia Indra; Fitria, Meutia Srikandi; Oktaviola, Vanny (Jurnal Teknologi Laboratorium, 2021)
Caulerpa racemosa is a green algae consumed by people in northern coastal areas. C. racemosa has a habitat attached to the shallow seabed. C. racemosa usualy consumed fresh without any cooking process so that the contamination of microorganisms can be eaten. Molecular identification using 16S rRNA is needed to determine the type of bacterial contaminants in C. racemosa. The isolates of C. racemosa were cultured in HIA, BAP, and BHI media. Bacteria from BHI media were isolated by DNA, PCR for 16S rRNA gene, and sequencing. Bacteria isolate C. racemosa was found to have the Î±-hemolytic ability in BAP media. The sequencing analysis showed that the three bacterial colonies of C. racemosa isolate had high similarity with V. parahemolyticus, Caldalkalibacillus mannanilyticus, and Exiguobacterium profundum.